جهود علماء المالكية من المفسرين والمحدثين في تحقيق وحدة النسيج الاجتماعي دولة الإمارات العربية المتحدة أنموذجا - عبد العزيز بن حسن بن عبد الله بنياي المرزوقي
The Almighty Allah sent Prophet Mohammed to guide humanity and preach monothe-ism i.e. worshiping Allah alone. Muslims were united on this belief and Allah urges them to keep united and reject disagreement and division. However, during the rule of the third Caliphate Othman Ibn Affan, there a strife erupted amongst the Muslims. Many sects and groups were formed and they started fighting each other leading to bloodshed and the loss of wealth and corruption spread across the Muslim nation. For this reason, many Muslim scholars have made remarkable efforts to reunite the Muslim society. In so doing, they authored books, held debates, delivered speeches and wrote letters to rulers warning the Muslims against the serious risks that face the Muslim nation because of this strife. On their part, the scholars who follow Maliki Madhab made considerable efforts to reunite the Muslim nation and restore its social fabric, and this was clear dur-ing the time of Imam Malik. Currently, the state of UAE has officially adopted this Madhab. As a result, UAE has become an ideal example in preserving unity and agree-ment amongst the Muslim scholars as well as the people in the state of UAE. Thus, the present study aims to show the importance of unity and the great efforts made by Maliki Madhab to reunite the Muslim society and address the problems that rapture its social fabric. Following the analytical inductive approach, the researcher analyses the Quranic and prophetic tradition texts to deduce the factors that lead to unity of the Muslim na-tion. The findings of the study suggests that the Maliki Madhab has an important role in maintaining the fabric of the Muslim nation on the one hand, as well as the success of UAE in preserving unity because of the wise founding leader, Sheik Zaid (may Allah have mercy on him).